PEMBERDAYAAN PETERNAK LEBAH TRIGONA PADA KELOMPOK USAHA A BEE HONEY DI GAMPONG ALUE AWE KECAMATAN MUARA DUA - M Muhammad; M Muhammad; Reza Putra; Abdul Rahman; Ridho Hafis; Faizar Rianda (Yayasan Hurriah, Banda Aceh, 2022)
As part of a pilot program, Trigona honey bees have been cultivated in Gampong Alue Awe, Muara Dua subdistrict, by the A Bee Honey group. Under certain conditions, the supply of honey does not satisfy the demand, despite the fact that the cultivation experience and revenue can be used as a source of income. The prices are relatively higher, and consumers have faith in the product's legitimacy and effectiveness. Moreover, unlike livestock farming, beekeeping does not require feed or labor. Gampong Alue Awe, still including woodland areas and community gardens, has the potential to be developed. In addition to a poorly understood sales process, the lack of understanding regarding the cultivation and economics of kelulut honey makes consumers less interested in it. Therefore, community service activities in the form of training are required to determine the function of kelulut honey cultivation in raising family income. According to the circumstance study, the community does not comprehend the advantages and potential of trigona bee cultivation. The purpose of the training is to educate the community about the potential of trigona bee culture as an alternative source of income. In Gampong Alue Awe, the requirement for additional breeders to meet honey stocks can become part of the government's food security policy. From August to November 2022, the group received assistance in the form of agriculture training, harvesting process care, mentoring, and colony support. To join the Bee Honey Breeders Club, you must be a member of the community. The group provides assistance and serves as a coach and incubator for the results of its members. Participants sell honey through the organization due to the fact that business and distribution licenses are already in place. As a result of the service, five family heads expressed interest in joining the program with the group and began raising trigona bees after receiving instruction. Gampong Alue Awe has cooperated with partners to incorporate this initiative into the Gampong budget as a food security program. The benefits of these activities offer a new source of revenue for the community, and the Tridharma of Higher Education seeks the formation of entrepreneurship in the community